377 THE NEWEST VITAL SIGN: COMPARING INSTRUMENTS TO SCREEN FOR LOW HEALTH LITERACY?. Issue 1 (1st January 2007) - Sweeney, A.; Bass, P. F.; Rodrigue, C. Z.; Osborn, C. Y.; Wolf, M. S.; Davis, K.; Bocchini, M.; Jain, S.; Davis, T. C.
Abstract : Background: The Newest Vital Sign (NVS) is a new rapid screening instrument for low literacy in medical settings. No studies currently compare the NVS with the Short Test of Functional Health Literacy in Adults (S-TOFHLA). Purpose: Compare the performance of the NVS to the S-TOFHLA and assess the operating characteristics of the NVS. Methods: A convenience sample of patients at two federally qualified health centers (FQHCs) were interviewed and given two literacy assessments, the S-TOFHLA and the NVS. The S-TOFHLA is a reading comprehension and numeracy assessment with well-studied internal consistency, reliability, and validity. Scores range from 0 to 100, with scores less than 53 identifying poor health literacy. The NVS is a nutrition label that tests patients' general literacy and numeracy skills with six questions. A score of 4 to 6 indicates adequate literacy. Results: Of the 119 patients tested, the average age was 55 years old (35-55), 70% were female, 61% were African American, and 39% had not graduated from high school. Administration time was approximately 7 minutes for the S-TOFHLA and 5 to 7 minutes for the NVS. The internal consistency of the NVS was good (α = 0.81). The correlation between scores on the NVS and scores on the S-TOFHLA was 0.61 ( p < .001). The area under the ROC curve for predicting inadequate health literacy according to the S-TOFHLA was 0.73 (95% CI 0.70-0.78). NVS scores of 0 to 1 had a sensitivity of 94.6% and a specificity of 63.4% for predicting inadequate health literacy according to the S-TOFHLA. The Table presents scores and percentages for each test. Conclusion: The NVS showed a moderate correlation with the highly validated S-TOFHLA and did well as a screen predicting low literacy as defined by the S-TOFHLA in two FQHCs.